ASSESSING SUBMARINE LANDSLIDE STATUS BY USING SEABED TOPOGRAPHY 3D MODEL AND FAULT STRUCTURE ON SOUTH CENTRAL VIETNAM’S CONTINENTAL SHELF - Thanh, Phi Truong; Dung, Tran Tuan (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of assessing submarine landslide status by using seabed topography 3D model and fault structure on South Central Vietnam’s continental shelf. On the 3D model, landslide evidences occur as narrow and straight steps along continental slope at the depths of 700 - 800 m, 1.200 - 1.300 m and 1.500 - 1.700 m; some landside blocks occur as different dome forms on the middle slope and slope foot. The landslide evidences are also identified on the perpendicular seismic profile  to slope surface and it is especially clear in the new-multibeam data of marine survey in 2013 of national  project KC09.11/11-15. Besides, the results of analyzing structural map of fault and reflected seismic profiles also show that, circular failure modes can occur along the continental slope in study. The boundary of failure blocks can be fault on the crest of slope and  unconformable surfaces. The different analytical results from the fault structure map in Quaternary also show that it is hard for plane failure mode on the fault surfaces to occur in this area, because the  dip angle of fault is always higher than slope angle. However, the occurrence of perpendicular faults to slope surface can break slope surface and increasingly cause submarine landslide in this area.